Evaluation of appendiceal mucinous neoplasms with a new classification system and literature review - Gündoğar, Özgecan; Kımıloğlu, Elife; Komut, Neslihan; Cin, Merve; Bektaş, Sibel; Gönüllü, Doğan; İlgün, Ahmet Serkan; Erdoğan, Nusret (Turkish Journal of Gastroenterology, 2018)
Abstract Appendiceal mucinous neoplasms constitute a diagnostic spectrum ranging from adenoma to mucinous adenocarcinoma. To date, many classification systems have been proposed to reflect the histomorphological diversity of neoplasms in this range and their clinical correspondence, and also to form a common terminology between the pathologist and clinicians. The aim of this review is to provide an updated perspective on the pathological features of appendiceal mucinous neoplasms. Using the 2016 Modified Delphi Consensus Protocol (Delphi) and the Eighth Edition of the American Joint Committee on Cancer (AJCC) Cancer Staging Manual, 19 cases presented from June 2011 to December 2016 were evaluated and diagnosed with appendiceal mucinous neoplasia. According to the Delphi, non-carcinoid epithelial tumours of the appendix were categorized in eight histomorphological architectural groups. These groups are adenoma, serrated polyp, low-grade appendiceal mucinous neoplasm, high-grade appendiceal mucinous neoplasm, mucinous adenocarcinoma, poorly-differentiated adenocarcinoma with signet-ring, signet-ring cell carcinoma and adenocarcinoma. The most common symptom was right lower quadrant pain. The median age of these cases was 60±15 years. There was a preponderance of females (F/M: 15/4). In our re-evaluation, six cases were diagnosed as serrated polyp. There were 11 cases in the LAMN group and two cases in the mucinous adenocarcinoma group. Using the Delphi and the AJCC manual, there were many changes in the classification, evaluation and treatment of appendiceal mucinous neoplasms. These classification systems have facilitated the compatibility and communication of clinicians and pathologists and have guided clinicians on treatment methods. Cite this article as: Gündoğar Ö, Kımıloğlu E, Komut N, et al. Evaluation of appendiceal mucinous neoplasms with a new classification system and literature review. Turk J Gastroenterol 2018; 29: 532-42.